2020
DOI: 10.21037/jtd.2020.03.60
|View full text |Cite
|
Sign up to set email alerts
|

Management of cardiovascular comorbidities in chronic obstructive pulmonary disease patients

Abstract: Chronic respiratory diseases (CRDs) cause enormous burden to the society. In 2016, these diseases were responsible for 3.8 million deaths or 7% of all global deaths. Seventy-five percent of these deaths occurred in those aged 30-69 years, demonstrating that CRDs are not solely a problem for the elderly (1). Chronic obstructive pulmonary disease (COPD) is a major CRD characterized by high prevalence and mortality, and by a persistent and usually progressive airflow limitation associated with different risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 112 publications
(117 reference statements)
0
9
0
3
Order By: Relevance
“…The combined analysis results of this study show that COPD patients have a higher risk of CHD, and COPD is a risk factor for CHD, which is consistent with the current research on the mechanism of CHD. Though the mechanisms by which COPD increases CHD risk are not clear, patients with COPD often display abnormally high concentrations of circulating systemic inflammatory could be the main reason, [3][4][5][6] and the lung hyperinflation also represent one of the most important problem related to the high thoracic pressure that could be generated. 14 However, public or health professionals and patients with COPD still generally have insufficient understanding of "COPD increases the risk of developing CHD," leading to poor prevention of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined analysis results of this study show that COPD patients have a higher risk of CHD, and COPD is a risk factor for CHD, which is consistent with the current research on the mechanism of CHD. Though the mechanisms by which COPD increases CHD risk are not clear, patients with COPD often display abnormally high concentrations of circulating systemic inflammatory could be the main reason, [3][4][5][6] and the lung hyperinflation also represent one of the most important problem related to the high thoracic pressure that could be generated. 14 However, public or health professionals and patients with COPD still generally have insufficient understanding of "COPD increases the risk of developing CHD," leading to poor prevention of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 COPD increases the risk of CHD due to chronic systemic/local inflammation. 1,[3][4][5][6] And traditional cardiovascular risk factors such as smoking, hypertension, hyperlipidemia are highly prevalent in patients with COPD, they could contribute to COPD progression. 7 Epidemiological studies have also shown that the incidence of cardiovascular death in patients with COPD is high.…”
Section: Introductionmentioning
confidence: 99%
“…This seems important given the high prevalence of comorbid course of COPD and atherosclerotic cardiovascular disease. Indeed, coronary heart disease and peripheral artery disease are common in COPD patients [ 68 , 69 ]. Such comorbidity mutually worsens the course of both diseases.…”
Section: Clinical Links Between Hdl and Copdmentioning
confidence: 99%
“…Изменения образа жизни и особенно пагубная роль курения в развитии ХОБЛ стали неотъемлемой частью проводимого ВОЗ 18 ноября каждого года Всемирного дня Международные аСПеКТы по борьбе с ХОБЛ. Поскольку ХОБЛ и ИБС часто встречаются у одного больного, общность подходов к лечению этих заболеваний очевидна, в частности снижение легочной функции тесно связано с высоким риском развития сердечной недостаточности, а большая часть больных с умеренными по тяжести формами ХОБЛ умирает от ССЗ чаще, чем от легочной недостаточности [31]. В соответствии со сказанным, непрерывная борьба с курением, регулярный контроль за заболеванием и интегральный подход к лечению ХОБЛ являются залогом сохранения достигнутого и дальнейшего снижения смертности от ХОБЛ.…”
Section: таблица 3 изменения образа жизни в странах с различным доходом на душу населенияunclassified